-5f/6-2/3=4/3

Simple and best practice solution for -5f/6-2/3=4/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5f/6-2/3=4/3 equation:


f in (-oo:+oo)

(-5*f)/6-(2/3) = 4/3 // - 4/3

(-5*f)/6-(2/3)-(4/3) = 0

(-5*f)/6-2/3-4/3 = 0

-5/6*f-2 = 0 // + 2

-5/6*f = 2 // : -5/6

f = 2/(-5/6)

f = -12/5

f = -12/5

See similar equations:

| 7d+3/5=-6d+3/5 | | 6-2d=2/5d+6/5 | | -5/7d+5/6=-7d+5/6 | | x+21/3=5 | | -7+k=6k-71/8 | | 6k-1/3=4/5k+53/75 | | -2/7m+1/2=6m-57/14 | | -1/2d+8=113/14+2/7d | | -8(t+3)=40 | | -3/8+5/7k=2/3k-173/504 | | 2/3x-5/8=-x-135/88 | | 2k+2=-13+7k | | -5x-9=-6x-12 | | 5k-3/7=k+69/35 | | -1/6n+4/9=-2/5n-13/18 | | 1-1/5d=6d-274/5 | | 1/4x+7=13/6-7x | | 2/5+1/2a=3/4a-7/20 | | 2+2/5d=-5d+307/5 | | 2m-6=-26+7m | | 4-b=-2/3b+1 | | x+17+3x=-13-3x-19 | | -1/4a-5=a-45/4 | | 2+5/6b=-b+23/6 | | 5/7-2x=2/7x+5/7 | | 6m-5/9=218/45-3/4m | | -3/8-6k=4/5k+1073/40 | | 3/4t+8=425/48-5/7t | | -1/5b+3/10=-2/7b+33/70 | | -a+1=-3/7a-33/7 | | 3/5+5/6n=2/3n+32/45 | | 9-6/7n=-5n+523/42 |

Equations solver categories